Generalized Oberst beam method for measuring viscoelastic parameters of layered composite components - Dobrucki, A.; Bolejko, R.; Nieradka, P.; Klimek, A. (Archives of Mechanics, 2023)
This paper proposes two new methods of measuring the viscoelastic parameters of materials. The methods are based on the composite beams' resonant frequencies measurement. The Young moduli and loss factors of the components are determined by measuring the frequency response of a composite beam twice, each time with different layer thickness ratios. A system of two equations is obtained, from which Young's moduli of the composite components are calculated. Similarly, two obtained equations determine the loss factors. The results obtained by the proposed methods are compared with those obtained by standard methods and then validated by experiments and FEM simulations. It was noted that the developed models, as well as the standard ones, are highly sensitive to the precision of the samples (material trimming and the way of joining the composite elements). The proposed methods prove to have an advantage over the standard ones in the matter of more frequent measurement criterion fulfilment. The acknowledged criterion represents the existence of a sensible solution insensitive to measurement errors. This criterion, which assures that the results are not prone to errors (for example negative loss factors) is met in 100% of cases in one of the methods, compared to 65% for standard methods.